Intramedullary fixation versus plate fixation in the treatment of midshaft clavicle fractures: a meta-analysis of randomized controlled trials - Lu, Minpeng; Qiu, Hao; Liu, Yuting; Dong, Jing; Jiang, Lingfang (Frontiers in Surgery, 2024)
Objective:The aim of this systematic review and meta-analysis is to assess the clinical efficacy of intramedullary fixation (IF) versus plate fixation (PF) in the treatment of midshaft clavicle fractures.:We conducted a computerized search of the electronic databases (PubMed, EMBASE, Cochrane Library, Medlineand Chinese Journal Full-text Database) from the establishment of the database to the end of November 2022. The quality of the included studies was assessed according to the Cochrane Collaboration's "Risk of bias". Comparisons between the two groups were based on 8 variables, including Constant score, disabilities of the arm, shoulder and hand (DASH) score, surgery time, length of incision, hospital stay; time to union, blood loss and infection.Results:Thirteen randomized controlled trials (RCTs) comprising a total of 928 patients were included in our meta-analysis. The pooled results showed that IF can benefit midshaft clavicle fractures with a reduced surgery time and hospital stay, a smaller incision, a better shoulder function(DASH score), shorter time to union and lower rate of infection compared with PF. However, there was no significant difference between the two groups in terms of Constant score at 12-month follow-up.IF is superior to PF for the treatment of midshaft clavicle fractures.